Molecular Characterization and Survive Abilities of Salmonella Heidelberg Strains of Poultry Origin in Brazil - Melo, Roberta T.; Galvão, Newton N.; Guidotti-Takeuchi, Micaela; Peres, Phelipe A. B. M.; Fonseca, Belchiolina B.; Profeta, Rodrigo; Azevedo, Vasco A. C.; Monteiro, Guilherme P.; Brenig, Bertram; Rossi, Daise A. (Frontiers in Microbiology, 2021)
The aim of the study was to evaluate the genotypic and phenotypic characteristics of 20 strains of S. Heidelberg (SH) isolated from broilers produced in southern Brazil. The similarity and presence of genetic determinants linked to virulence, antimicrobial resistance, biofilm formation and in silico-predicted metabolic interactions revealed this serovar as a threat to public health. The presence of the ompC, invA, sodC, avrA, lpfA, and agfA genes was detected in 100% of the strains and the luxS gene in 70% of them. None of the strains carries the blaSHV, mcr-1, qnrA, qnrB and qnrS genes. All strains showed a multidrug-resistant profile to at least 3 non--lactam drugs, which include colistin, sulfamethoxazole, and tetracycline. Resistance to penicillin, ceftriaxone (90%), meropenem (25%), and cefoxitin (25%) were associated with the presence of blaCTX-M and blaCMY-2 genes. Biofilm formation reached a mature stage at 25°C and 37°C, especially with chicken juice (CJ) addition. The sodium hypochlorite 1% was the least efficient in controlling the sessile cells. Genomic analysis of two strains identified more than 100 virulence genes and the presence of resistance to 24 classes of antibiotics correlated to phenotypic tests. Protein-protein interaction (PPI) prediction shows two metabolic pathways correlation with biofilm formation. Virulence, resistance, and biofilm determinants must be constant monitoring in SH, due to the possibility of occurring infections extremely difficult to cure and due risk of the maintenance of the bacterium in production environments.